2017
DOI: 10.3892/mmr.2017.7567
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin decreases traumatic injury of the spinal cord and exhibits antioxidant and anti-inflammatory activities in a rat model via inhibition of COX-2, TGF-β1, p53 and elevation of Bcl-2/Bax signaling pathway

Abstract: Myricitrin has multiple effects, including antagonism of platelet activating factor, regulation of blood sugar levels, oxidation resistance, protection of the liver and the relieving of ethylism. The present study evaluated how myricitrin weakens traumatic injury of the spinal cord (TISC), and exhibits antioxidant and anti‑inflammatory activities in a rat model. TISC model rats were injected intraperitoneally with 5, 10 or 30 mg/kg/day of myricitrin for 5 days. Basso‑Beattie‑Bresnahan evaluation of locomotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Myricitrin ameliorated loss of dopaminergic neurons, preserved the activity of tyrosine hydroxylase and suppressed the inflammatory response by attenuating TNF-α expression in activated microglia [261]. Its protective effects were also documented in traumatic injury of the spinal cord where myricitrin exerted strong anti-oxidative effects, reduced neuroinflammation, restored p53 expression and decreased the Bax/Bcl-2 ratio [262]. Regarding its anti-oxidative effects, myricitrin reversed the increase in MDA, as well as the activation of SOD, catalase and GSH-Px, whereas its anti-inflammatory effects were reflected in the inhibition of spinal cord injury-induced expression of the NF-κB p65 subunit, TNF-α, IL-1β and IL-6.…”
Section: Myricitrinmentioning
confidence: 89%
See 1 more Smart Citation
“…Myricitrin ameliorated loss of dopaminergic neurons, preserved the activity of tyrosine hydroxylase and suppressed the inflammatory response by attenuating TNF-α expression in activated microglia [261]. Its protective effects were also documented in traumatic injury of the spinal cord where myricitrin exerted strong anti-oxidative effects, reduced neuroinflammation, restored p53 expression and decreased the Bax/Bcl-2 ratio [262]. Regarding its anti-oxidative effects, myricitrin reversed the increase in MDA, as well as the activation of SOD, catalase and GSH-Px, whereas its anti-inflammatory effects were reflected in the inhibition of spinal cord injury-induced expression of the NF-κB p65 subunit, TNF-α, IL-1β and IL-6.…”
Section: Myricitrinmentioning
confidence: 89%
“…Regarding its anti-oxidative effects, myricitrin reversed the increase in MDA, as well as the activation of SOD, catalase and GSH-Px, whereas its anti-inflammatory effects were reflected in the inhibition of spinal cord injury-induced expression of the NF-κB p65 subunit, TNF-α, IL-1β and IL-6. Ultimately, its protective effects were observed at the histological level and in locomotor activity [262]. Although the neuroprotective effects of myricitrin have not been explored sufficiently, its anti-oxidative and anti-apoptotic effects have been described in other types of cells.…”
Section: Myricitrinmentioning
confidence: 99%
“…Documents studies showed myricitrin regulates several extracellular signalling pathways, such as STAT3, PI3K/Akt/eNOS and ERK/p53 The most recently study showed myricitrin inhibited osteoporosis of ovariectomized rats, which was associated with reducing the expression of IL‐6 and partially suppressing ROS production . In complementary to these findings, we performed F‐actin ring formation and bone absorption assay in vitro to explore the inhibitory effects of myricitrin on osteoclast differentiation and further investigate the underlying mechanisms involved in these down‐regulation effects.…”
Section: Discussionmentioning
confidence: 81%
“…Otherwise, recently studies have showed myricitrin regulates various cellular signalling cascades including STAT3 and PI3K/Akt/eNOS . Moreover, myricitrin demonstrated suppression effects on myocardial apoptosis relied on the ERK/p53‐mediated mitochondrial apoptosis pathway . Furthermore, the most recently study showed the protective effects of myricitrin against osteoporosis via reducing the expression of IL‐6 and partially suppressing ROS production .…”
Section: Introductionmentioning
confidence: 99%
“…Myr, a flavonoid compound extracted from Myrica rubra , exhibits anti-inflammatory, antioxidant, and anti-fibrotic effects. Myr can inhibit the expression of iNOS and COX-2, thereby blocking NO and PEG 2 production in IL-1β-stimulated OA rats [ 111 , 131 ]. Immunohistochemical analysis showed that the anti-inflammatory effects of Myr were based on the interference of IL-1β-activation of NF-κB and MAPK signaling pathways.…”
Section: No In Oa Treatmentmentioning
confidence: 99%